Illustrated textbook of paediactrics - Lissauer, Tom; Clayden, Graham
This is the fourth edition of a highly popular 'must have textbook for paediatrics for medical students'. The previous edition has been translated into eight languages and also won British Medical Association and Royal Society of Medicine prizes for the best paediatrics textbook.